National Bond Microfinance Program in Welfare Organization of Iran; Goals, Service Pattern, Challenges, and Future Path - Behzad Damari; Alireza Heidari; Habibollah Masoudi-Farid; Arezoo Zokaei (Shahid Beheshti University of Medical Sciences, 2020)
Background and Objective: Despite the establishment of various institutions and organizations in the realization of women's rights and education, and despite the considerable costs, women are suffering from the problems of economic and cultural poverty. Therefore, the Welfare Organization decided to alleviate their problems with the national microfinance program. The purpose of this study was to explain the goals, service model, challenges, and future path of this national program in the Welfare Organization. Materials and Methods: A qualitative study was conducted in 2016. Participants included managers and experts of Welfare organization in 31 provinces of the country, 21 members of public mediators and collaborative and stakeholder organizations, and five senior managers of social deputy in the Welfare Organization. Data were collected using document analysis and interviews with experts and analyzed by the content analysis method. Results: The national microfinance program was implemented with the aim of expanding the family economy, utilization of villagers with unsecured bank loans and empowering them, and promoting employment, micro-businesses, and enhancing the savings and banking skills of the target group. The unfamiliarity of external stakeholders, the troubled banking system, the short-term outlook, and the inflexibility of managers and the transfer of duties to the private sector were identified as program challenges. The executive strategies include increasing financial support from self-help groups, reducing interest rates on loans paid by the Agricultural Bank, opening an account in the name of the group, repaying loans in installments, increasing awareness of the legality of the program, increasing the percentage of local executives' fees and creating an entrepreneurial spirit. Conclusion: Despite the services provided in the microfinance program, it faces challenges at the government and external stakeholders and banking laws. To improve the current status, implementation of suggested solutions along with revision and modification of related processes is necessary.